A survey on oral hygiene practices among Malaysian adults - Esa, R.; Razak, I.A.; Jallaudin, R.L.; Jaafar, N. (1992)
A survey on oral hygiene practices was conducted on 537 dentate adult patients aged 15 years and over. The aim of this study was to investigate the variation in dental behavior with regards to socio-demographic factors, namely age, sex, ethnicity, income, education and occupational status. Patients attending nine randomly selected government dental clinics were interviewed on their daily oral hygiene practices. The majority (89.7) of the subjects reported that they brushed their teeth, 68 used toothpaste containing fluoride, but only 8.4 flossed their teeth. Generally the younger group had better oral hygiene habits. The higher the socioeconomic status of the adults, the better their toothcleaning practices. Awareness concerning dental floss was low regardless of all the socio-demographic variables. It was concluded that there is a need to improve the dental health practices of adults in Malaysia.